Adhesion at asphalt-aggregate interface through surface energy - Infante, Ana Sofia Figueroa; Lizcano, Fredy Reyes; Leal, Néstor Cely (Transportes, 2020)
One of the most common problems pavements have is the loss of adhesion and cohesion due to moisture damage. Tropical countries and rainy seasons are some of the causes for this type of distress on roads. Another factor that has high influence in this damage is the mineralogy of the aggregate. This research shows the results of adhesion and cohesion between the aggregates from a limestone quarry and two types of sandstones from different quarries, highly used for roads projects from Colombia, and the asphalt 60-70 (1/10) mm, same PG58-22. For determining the adhesion and cohesion, Bitumen Bond Strength tests were made for dry and wet conditions. In addition, the Surface Free Energy was measured for the aggregates and the asphalt. The results indicated that those type of aggregates are highly susceptible to moisture damage, due all values of humidity Index Damage (HDI) were less than 0,5. This indicates that it is necessary to use modifiers for controlling the stripping of the pavements due to Moisture Damage.